Performance Analysis of Revenue and Expenditure Budget Realization - Maulidnda, Dian Fathania; Deviyanti, Dwi Risma; Pattisahusiwa, Salmah (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this study is to determine the financial performance of the Balikpapan City Government for the 2016-2018 fiscal year based on five financial ratios, namely: regional financial independence, regional financial dependence, degree of decentralization, effectiveness and efficiency of regional original revenue. The analysis tools used for this study were the ratio of regional financial independence, regional financial dependence, degree of decentralization, effectiveness and efficiency of regional original income. The type of data in this study is quantitative data. The data source is secondary data. Based on the results of the research and analysis obtained for the ratio of regional financial independence levels is still low, the ratio of regional financial dependence is very high, the ratio of degrees of decentralization is still not optimal, the effectiveness ratio looks very effective, and the efficiency ratio looks less efficient